First in vitro and in vivo experiences with stay.safe balance, a pH-neutral solution in a dual-chamber bag - Lage, Cristina; Pischetsrieder, Monika; Aufricht, Christoph; Jörres, Achim; Schilling, Holger; Passlick-Deetjen, Jutta (Peritoneal Dialysis International, 2000)
In addition to low pH and high osmolarity, glucose degradation products (GDPs) are considered to play a major role in the bioincompatibility of peritoneal dialysis fluids (PDFs). The formation of GDPs can be reduced by separating the glucose component of the solution (kept at very low pH) from the lactate component of the solution (kept at alkaline pH) during sterilization and storage. This development has been achieved by the use of a dual-chambered bag. Immediately before infusion, the seam between the two chambers is opened, and the contents are mixed. The result is a fluid with a more physiologic pH in the range 6.8 – 7.4. Concentrations of 3-deoxyglucosone (3-DG), methylglyoxal (MG), acetaldehyde (AA), and formaldehyde (FA) in Stay·Safe Balance (Fresenius Medical Care, Bad Homburg, Germany) were remarkably reduced when compared to conventional PD solution [conventional PDF (1.5% glucose): 172 μmol/L, 6 μmol/L, 152 μmol/L, and 7 μmol/L respectively; Stay·Safe Balance (1.5% glucose): 42 μmolL, < 1 μmol/L, < 2 μmol/L, and < 3 μmol/L respectively; conventional PDF (4.25% glucose): 324 μmol/L, 10 μmol/L, 182 μmol/L, and 13 μmol/L respectively; Stay·Safe Balance (4.25% glucose): 60 μmol/L, < 1 μmol/L, < 2 μmol/L, and < 3 μmol/L respectively). Human peritoneal mesothelial cells (HPMCs) were exposed to a control solution, a conventional PDF [CAPD 2, 1.5% glucose (Fresenius Medical Care, Bad Homburg, Germany)], and Stay·Safe Balance, either in a co-incubation model (24-hour PDF exposure) or in a  re-incubation model (30-min PDF exposure), followed by 24-hour recovery in culture medium. Interleukin-1β (IL-1β)–stimulated (1 ng/mL) IL-6 secretion from HPMCs was assessed by ELISA. Exposure of HPMCs to conventional PDF resulted in a significant reduction in IL-6 release, which was fully restored following exposure to Stay·Safe Balance. In addition to the short-term investigations, long-term in vitro studies were also carried out. All fluids had near-neutral pH and were changed every second day. After 1, 3, 5, 7, 10, and 13 days of exposure, cell viability was assessed. Whereas exposure to conventional PDF resulted in a significant reduction in HPMC viability after just 3 – 5 days, no significant toxicity of filter-sterilized or dual-chambered fluid was observed for up to 13 days. An observational study with 9 patients suggested that the efficacy of Stay·Safe Balance is equivalent to that of conventional solution. However, even short-term treatment (8 ± 1 weeks) with this more biocompatible solution seems to improve mesothelial cell mass as indicated by a rise in cancer antigen 125 (CA125) from a baseline of 47 ± 37 U/min to 172 ± 90 U/min. Our data indicate that Stay·Safe Balance may help to better preserve peritoneal membrane cell function. An ongoing European multicenter study is expected to confirm these results.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.firsti
Keywords: Biocompatibility; glucose degradation products; advanced glycosylation end-products; pH-neutral peritoneal dialysis solution